2020
DOI: 10.1186/s12874-020-01108-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different lookback periods on the sociodemographic structure of the study population and on the estimation of incidence rates: analyses with German claims data

Abstract: Background Defining incident cases has always been a challenging issue for researchers working with routine data. Lookback periods should enable researchers to identify and exclude recurrent cases and increase the accuracy of the incidence estimation. There are different recommendations for lookback periods depending on a disease entity of up to 10 years. Well-known drawbacks of the application of lookback periods are shorter remaining observation period in the dataset or smaller number of cases. The problem o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…Including only one overall health variable cannot account for the observed differential health-dependent dropout. Another strategy to perform longitudinal analyses and avoid this bias is to use other data sources that do not suffer from selective health dropout, like claims or health insurance data, which however might also be susceptible to other biases [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Including only one overall health variable cannot account for the observed differential health-dependent dropout. Another strategy to perform longitudinal analyses and avoid this bias is to use other data sources that do not suffer from selective health dropout, like claims or health insurance data, which however might also be susceptible to other biases [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This selectivity increases with the length of lookback period applied. However, the study shows that the selectivity bias remains acceptable when lookback periods of 1 year are used ( 25 ). Furthermore, we additionally applied the minimum two quarter criterion to outpatient diagnoses, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Longer look-back periods would have reduced this proportion. However, a recent study has shown that there is always a trade-off between the length of look-back periods and the resulting shift in the socio-demographic structure of the insurance population [ 50 ]. This shift is caused by more rigorous preconditions on the length of the observation time, which must be met when longer look-back periods are applied.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, individuals with shorter insurance histories would have to be excluded, leading to an increasingly selective study population. However, the shift in the sociodemographic distribution remains minor when look-back periods of one year are applied [ 50 ].…”
Section: Discussionmentioning
confidence: 99%